THE TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN THE DIGITAL AGE: A LEGAL ANALYSIS OF THE PROTECTION OF EMPLOYEES’ PERSONAL DATA AND COMPLIANCE WITH LABOUR REGULATIONS FOLLOWING THE 2022 PERSONAL DATA PROTECTION ACT - Gunawan Widjaja (Adisam Publisher, 2026)
Digital transformation has revolutionised Human Resource Management (HRM) from an administrative function into a data-driven strategic ecosystem utilising artificial intelligence, predictive analytics, and integrated systems. However, the adoption of this technology poses serious legal challenges regarding the protection of employees’ personal data amidst the unequal power dynamics between employers and employees. This study aims to analyse digital transformation in HRM and the legal implications of Law No. 27 of 2022 on Personal Data Protection (PDP Law) for compliance with labour regulations in Indonesia. It employs a literature review (library research) using a legal-normative approach. The research findings indicate that digital transformation in HRM—encompassing AI-based recruitment, HRIS, digital monitoring, and biometrics—has enhanced efficiency whilst simultaneously creating massive privacy risks for workers. The 2022 PDP Act reshapes the labour law landscape by designating employers as Data Controllers who must adhere to the principles of purpose limitation, multi-layered data security, transparency, and structural accountability. This regulation curtails employers’ prerogatives through a proportionality test and strengthens workers’ rights to access, rectification, erasure, and data portability. Compliance with the 2022 PDP Act demands a fundamental overhaul of HR policies, investment in cybersecurity, the appointment of a Data Protection Officer (DPO), and the implementation of Privacy by Design. This study concludes that the success of digital transformation in HRM is not only measured by operational efficiency, but by the organisation’s ability to integrate technological innovation with the protection of workers’ human rights, thereby realising a fair, safe, and legally certain working ecosystem in the digital economy era.